An experimental investigation of the effects of cyclic transient loads on a turbocharged diesel engine. (1st January 2017) - Yum, Kevin Koosup; Lefebvre, Nicolas; Pedersen, Eilif
Highlights: The effects of cyclic loads on the BSFC and NOx emissions of a CI engine are investigated. Compared to static loads, the largest deviations are 6.7% and 9.1%, respectively. For the quasi-steady estimations, the largest errors are 2.9% and 4.3%, respectively. The effects primarily depend on the average load level. The quasi-steady estimations show good results except for a low load with high frequency. Abstract: This paper presents the results of the experimental investigation on the effect of cyclic transient loads on a turbocharged diesel engine with respect to fuel efficiency and NOx emissions. The transient loads in this test program are time varying torque in the form of a sinusoidal wave with a fixed amplitude at different frequencies and different mean values. The measurements from the transient tests are compared to the cases of constant loads and to estimations provided by a quasi-steady mapping. The largest influences are found at the lowest mean load (24.6%) and the highest frequency (0.2 Hz). For fuel efficiency, the transient deviation is 6.7%, while the estimation error is −2.9%. For NOx measurement in volume fraction, they are −9.1% and 4.3%, respectively. The results also show that the magnitude of the effect grows as the mean power load decreases. Finally, a graphical method is presented to evaluate the effect of load shifting operations for a diesel engine using the steady-state fuel consumption rate curve.